2017
DOI: 10.1177/1934578x1701201021
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition of Leaf extracts of Ailanthus altissima (Simaroubaceae) with Antibacterial and Antifungal Activity Equivalent to Standard Antibiotics

Abstract: Extracts of fresh and dry Ailanthus altissima leaves from Croatia were evaluated for their phenolic composition, antioxidant and antimicrobial activities. The methanolic extract had a higher concentration of total phenolics, flavonoids and non-flavonoids, as well as a higher antioxidant capacity than water extracts. Flavonoids identified in A. altissima leaves belong to two groups: flavones (glycosides of apigenin and luteolin) and flavonols (glycosides of quercetin and kaempferol). They were mainly present as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…Various factors affect the content of phenolic compounds and antioxidant activity in A. altissima extracts: selected tissue or organ (Luis, Gil, Amaral, Domingues & Duarte, 2012;Aissani et al, 2018), growing conditions (Vidović, Morina, Milić & Veljović Jovanović, 2015), extraction solvent (Luis et al, 2012;Poljuha et al, 2017;Aissani et al, 2018), and processing conditions (Poljuha et al, 2017). According to several authors (Luis et al, 2012;Albouchi et al, 2013;Poljuha et al, 2017;Aissani et al, 2018) leaves and bark of A. altissima are rich sources of polyphenolic compounds and possess very strong antioxidant activity. Presented work is in agreement with the results obtained in our study that reveal that the bark extract possessed ten times higher content of total phenolics and total tannins compared to leaf extracts.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Various factors affect the content of phenolic compounds and antioxidant activity in A. altissima extracts: selected tissue or organ (Luis, Gil, Amaral, Domingues & Duarte, 2012;Aissani et al, 2018), growing conditions (Vidović, Morina, Milić & Veljović Jovanović, 2015), extraction solvent (Luis et al, 2012;Poljuha et al, 2017;Aissani et al, 2018), and processing conditions (Poljuha et al, 2017). According to several authors (Luis et al, 2012;Albouchi et al, 2013;Poljuha et al, 2017;Aissani et al, 2018) leaves and bark of A. altissima are rich sources of polyphenolic compounds and possess very strong antioxidant activity. Presented work is in agreement with the results obtained in our study that reveal that the bark extract possessed ten times higher content of total phenolics and total tannins compared to leaf extracts.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Kaempferol-3-rutinoside is reported as bitter-tasting flavonol glycoside with a wide range of antioxidants, anticancer, and antibacterial potential. [58,59] In addition, Linolenic acid was also present in the extract of Khalas date, a research demonstrated that linoleic acid effectively inhibited Mycobacterium tuberculosis. [60] ).…”
Section: Resultsmentioning
confidence: 99%
“…Acetone extract from leaves displayed activity against Escherichia coli. Acetone, methanol and dichloromethane extracts had high activity towards Candida albicans (Poljuha et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…These extracts are efficient against Gram-positive bacteria (Albouchi et al, 2013) and inactive towards Gram-negative bacteria and Candida albicans. They also exhibited high inhibiting effect on germination and growth of rots of wild carrot Daucus carota L. Phenol components of extracts from leaves of A. altissima (methanol and aqueous extracts), their antibacterial and anti-fungal properties were studied by Poljuha et al (2017). Methanol extract contained more phenol, phlavonoid and nonphlavonoid compounds, and also had more notable antioxidant activity than aqueous extracts.…”
Section: Discussionmentioning
confidence: 99%